EKSPLORASI HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KELELAHAN SPIRITUAL PADA MAHASISWA - Afiffah, A; Salsabila, Aisyah; Salma, Nasywa (MAMBA'UL 'ULUM, 2025)
This study explores the relationship between the intensity of social media use and the emergence of spiritual fatigue among Muslim university students in the digital era. Using the Conservation of Resources (COR) Theory (Hobfoll, 1989) as the analytical framework, this study highlights how excessive digital engagement can deplete essential spiritual resources such as time for worship, self-reflection, and strengthening one’s connection with Allah. The findings reveal that uncontrolled social media use leads to inner distress and diminished spiritual well-being. Theoretically, this study extends the COR Theory to Islamic spirituality by showing that spiritual resources are as vulnerable to depletion as psychological ones. Practically, the research underscores the importance of self-regulation and muraqabah (spiritual awareness) in maintaining balance between online activities and devotion. Islamic higher education institutions are encouraged to promote digital literacy programs focused on spiritual resilience. This study contributes to the development of contemporary Islamic scholarship (Tsaqofah Islamiyah) and provides new insights into the dual role of social media—as both a source of spiritual reinforcement and depletion.